A rare case of leaking thoracic aortic aneurysm in a patient with massive pulmonary embolism - Shabib Al-Zuabi; Alexander P. Varkey; Safia F. Abdalmaksoud; Hadeel S. Alothman; Ibrahim Alrashdan (SpringerOpen, 2013)
The aim of this study was to report a rare case of a leaking thoracic aorta aneurysm in a female patient with massive pulmonary embolism. A 70-year-old woman with hypertension who had suffered a cerebral vascular accident 2 years ago presented with urinary tract infection, dehydration, and anemia. While in hospital, she was diagnosed with pulmonary embolism, and anticoagulation therapy was started using heparin. As the tachycardia persisted with a further drop in hemoglobin levels, and because a new left-sided pleural effusion was revealed on chest radiograph, a chest CT with a CT angiography was performed. It revealed a large leaking aneurysm of the descending thoracic aorta. This was treated by inserting an endovascular stent. This rare case shows the importance of investigating for other serious coexistent causes of tachycardia in patients with pulmonary embolism during treatment.